Impact Of an Educational Intervention Program on Knowledge and Perceptions of College Students Towards HIV/AIDS In Anand - Manisha K Gohel; Uday Singh S; Ajay Phatak (Medsci Publications, 2016)
Introduction: An estimated 5.4 million young people aged 15-24 were living with HIV and 780,000 were newly infected with HIV in 2012.Rapid modernization coupled with the fact that comprehensive sex education is practically non-existant among youth makes them quite vulnerable. Objective: To assess the impact of an educational intervention program on the knowledge and perceptions about HIV/AIDS among students. Methods: The study was conducted in four colleges in Vallabh Vidhyanagar, Gujarat. A pre-tested structured proforma based on Adolescent AIDS Knowledge Scale was used to assess the knowledge & perceptions regarding HIV/AIDS before and after the educational intervention. Descriptive statistics were used to depict the perceptions and paired t test was used to estimate the impact of the intervention. Results: Total of 510 (63.7% females, 36.3% males) students from 4 different streams participated in the study. The mean(SD) post-test (12.78[0.93]) HIV/AIDS knowledge score was significantly higher than pre-test (8.98[2.71]) score (p<0.001). The perceptions were restrictive and solutions perceived were extreme. Linkage between HIV and immoral conduct was not highly perceived by the students. Conclusion: A simple interactive educational intervention can improve understanding of HIV/AIDS among students.Similar models with appropriate cultural adaptation should be implemented to empower youth regarding HIV/AIDS.